2017
DOI: 10.26858/est.v3i3.4130
|View full text |Cite
|
Sign up to set email alerts
|

Geometry Skill Analysis In Problem Solving Reviewed From The Difference Of Cognitive Style Students Junior High School

Abstract: This study aimed to analyze the geometry skills in solving problems in terms of cognitive styles differences in the students of SMP Negeri Urumb. The type of this research is descriptive research that is qualitative with case study approach. The subject of this research is all students of SMP Negeri Urumb. (1) Subject selection is done by using snowball sampling technique. The main instrument in this study is the researchers themselves and accompanied by supporting instruments such as diagnostic tests, geomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 2 publications
0
8
0
1
Order By: Relevance
“…Students are given 15 minutes to complete the questions. Warli (Nur & Nurvitasari, 2017) made the criteria for students' cognitive style after completing the MFFT test as shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Students are given 15 minutes to complete the questions. Warli (Nur & Nurvitasari, 2017) made the criteria for students' cognitive style after completing the MFFT test as shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The problem-solving process can also be determined by cognitive style, namely the response that a person gives when facing a problem in the viewpoint, the time required and response accuracy, or the dominant method used to respond (Nur & Nurvitasari, 2017). Cognitive styles are divided into four cognitive styles (Haghighi et al, 2015), namely; impulsive, slow inaccurate, fast accurate, and reflective.…”
Section: Introductionmentioning
confidence: 99%
“…Since the GEFT was published, some scholars have tested and employed it, and it shows a strong correlation ranging from .60 to .90 (Fyle, 2009;Jantan, 2014;Lis & Powers, 1979;Panek et al, 1980;Witkin et al, 1971). This correlation remains strong even when it is translated in Indonesian (Kamaruddin et al, 2004;Nugraha & Awalliyah, 2016;Puspananda & Suriyah, 2017) and employed in the Merauke Regency (Nur & Palobo, 2018;Nur & Nurvitasari, 2017). Puspananda and Suriyah (2017) in their research on factor analysis on the GEFT to measure cognitive styles found that the GEFT instrument has one dominant dimension, namely, cognitive styles.…”
Section: Population and Samplementioning
confidence: 99%
“…The validity and reliability show the internal consistency of the GEFT, and, therefore, GEFT is ready to use (Puspananda & Suriyah, 2017). This consideration led our study to use a translated version of GEFT (Kamaruddin et al, 2004;Nur & Nurvitasari, 2017) without testing it.…”
Section: Population and Samplementioning
confidence: 99%
“…The internal factor was the students psychology and mental or readiness to learn, whereas the external factor was the environment and instrumental (eg curriculum, learning program, activity, teacher, and facility) [23]. In addition, traditional geometry learning through lecture using school textbooks has not assisted yet students in understanding geometry concepts [24].…”
Section: B Van Hiele Phase-based Learningmentioning
confidence: 99%